Застосування лідарного сканування при створенні цифрової моделі рельєфу - Левченко, В. О.; Бутенко, Євген Володимирович (НУБіП України, 2023)
Laser scanning systems (hereinafter referred to as LSS) have been developing rapidly in recent years and have long been successfully used in various countries to monitor the environment and spatial analysis of territories. LiDAR (Light Induced, Detection and Ranging) is a technology for obtaining and processing information about remote objects using active optical systems that use the phenomena of light reflection and scattering in transparent and translucent media. Laser scanning systems provide fast, accurate and relatively cheap surveying of the terrain, and less time and effort is spent on processing the information, which confirms the fact that Ukraine needs to develop in this branch of science researching.
Keywords: цифрова модель рельєфу; digital terrain model; digitales Geländemodell; лідарне сканування; Lidar-Scannen; lidar scanning